A novel panel of serum miR-21/miR-155/miR-365 as a potential diagnostic biomarker for breast cancer - Han, Ji-Guang (Ann Surg Treat Res, 2017)
PURPOSE: Insufficient sensitivity and specificity prevent the use of most existing biomarkers for early detection of breast cancer. Recently, it was reported that serum microRNAs (miRNAs) may be potential biomarkers in many cancer diseases. In this study, we investigated whether serum levels of 5 miRNAs including miR-21, miR-125b, miR-145, miR-155, and miR-365 could discriminate breast cancer patients and healthy controls. METHODS: Serum levels of miRNAs were measured by using quantitative real-time polymerase chain reaction in 99 breast cancer patients and 21 healthy controls. The abundance change of serum miRNAs were also evaluated following surgical resection in 20 breast cancer patients. Receiver operating characteristic (ROC) curve analysis was performed to assess the sensitivity and specificity of miRNAs as diagnostic biomarkers. RESULTS: Serum levels of miR-21 and miR-155 was significantly higher, while miR-365 was significantly lower in breast cancer as compared with healthy controls. The serum levels of miR-21 and miR-155 significantly decreased following surgical resection. Additionally, the serum level of miR-155 at stages I and II was significantly higher compared to stage III. The serum miR-145 level was remarkably higher in progesterone receptor (PR)-positive patients than PR-negative. The positivity of miR-21, miR-155, and miR-365 was high compared to CA 153 and CEA in breast cancer. ROC curve analyses of a combination of miR-21, miR-155, and miR-365 yielded much higher area under curve and enhanced sensitivity and specificity in comparison to each miRNA alone. CONCLUSION: The combination of serum miR-21/miR-155/miR-365 may potentially serve as a sensitive and specific biomarker that enables differentiation of breast cancer from healthy controls.